Morphology and Histology of Lyonet's Gland of the Tropical Tasar Silkworm, Antheraea mylitta - Patra, Sudip (University of Wisconsin Library, 2012)

(untitled)
The morphology and histology of Lyonet's gland in the second to fifth instar larvae of Antheraea mylitta Drury (Lepidoptera: Saturniidae) are described. Each of the paired silk glands of this silk worm were associated with a Lyonet's gland. The paired Lyonet's glands were located on the ventrolateral sides of the esophagus, close to the subesophageal ganglion. Whole mount and SEM observations revealed that each Lyonet's gland consisted of a rosette of glandular mass, and a short narrow tubular duct opening into the anterior part of the silk gland (ASG), close to the common excretory duct. In each instar, these glands were unequal in size. The glandular mass was innervated by fine nerves from the subesophageal ganglion, suggesting a neural control for the glandular activity. The glandular mass was made up of clustered long cells wrapped by a thin basal lamina, which was continuous over the non-secretory low columnar cells of the Lyonet's gland duct and ASG. The narrow bases of long cells of each glandular mass led into the lumen of the duct of the gland. Histochemical analysis of fully developed Lyonet's gland showed clustered lipid granules in the gland cells.